Circulating Interferon-Gamma Levels Are Associated with Low Body Weight in Newly Diagnosed Kenyan Non-Substance Using Tuberculosis Individuals - Nathan Shaviya; Valentine Budambula; Mark K. Webale; Tom Were (Interdisciplinary Perspectives on Infectious Diseases)
Although interferon-gamma, interleukin-10, and adiponectin are key immunopathogenesis mediators of tuberculosis, their association with clinical manifestations of early stage disease is inconclusive. We determined interferon-gamma, interleukin-10, and adiponectin levels in clinically and phenotypically well-characterised non-substance using new pulmonary tuberculosis patients (n=13) and controls (n=14) from Kenya. Interferon-gamma levels (P<0.0001) and interferon-gamma to interleukin-10 (P<0.001) and interferon-gamma to adiponectin (P=0.027) ratios were elevated in tuberculosis cases. Correlation analyses in tuberculosis cases showed associations of interferon-gamma levels with body weight (ρ=-0.849; P<0.0001), body mass index (ρ=0.664; P=0.013), hip girth (ρ=-0.579; P=0.038), and plateletcrit (ρ=0.605; P=0.028); interferon-gamma to interleukin-10 ratio with diastolic pressure (ρ=-0.729; P=0.005); and interferon-gamma to adiponectin ratio with body weight (ρ=-0.560; P=0.047), body mass index (ρ=-0.604; P=0.029), and plateletcrit (ρ=0.793; P=0.001). Taken together, our results suggest mild-inflammation in early stage infection characterised by upregulation of circulating interferon-gamma production in newly infected TB patients.